The Tiny and the Fragmented. Miniature, Broken, or Otherwise Incomplete Objects in the Ancient World - S. Rebecca Martin; Stephanie M. Langin-Hooper (Les Carnets de l’ACoSt)
Miniature and fragmentary objects are both eye-catching and yet easily dismissed. Tiny scale entices users with visions of Lilliputian worlds. The ambiguity of fragments intrigues us, offering tactile reminders of reality's transience. Yet, the standard scholarly approach to such objects has been to see them as secondary, incomplete things, whose principal purpose was to refer to a complete and often life-size whole.